Identification and determination of traditional medicinal plants of Southeast Sulawesi People at Arboretum Prof. Mahmud Hamundu Haluoleo University - Ruslin .; Sahidin I (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2008)
Seventeen traditional medicinal plants of South East Sulawesi are collected at Arboretum Prof. Mahmud Hamundu Universitas Haluoleo, have been determined successfully by Herbarium Bogoriense staffs, Cibinong Bogor. The plants came from Konawe and KonaweSelatan districts. Endemicity of those plants as medicinal plants were based on ethnobotanical study using information from “Tokoh Masyarakat Tolaki” and “Tokoh Masyarakat Jawa”. Collected traditional medicinal plants at those places, but have not known in Java, are assumed as specialized plants of Tolakinese. All of the plants were determined at Herbarium Bogoriense. Moreover, detailed study of those plants including biology, chemistry and pharmacy aspects were done by electronically literatures study using science direct programmed. According to the literatures, Sterculea cf. oblongata R.Br. and Talinum triangulare Willd have not been reported the research yields. Key words: Traditional medicinal plants, Konawe, Konawe Selatan, and Tolakinese.